Lithuanian Art 1989-1999 : The Ten Years. - Andriuskevicius, Alfonsas; Grigoraviciené, Erika; Jablonskiene, Lolita; Kuizinas, Kestutis; Malasauskas, Raimundas; Valatkevicius, Jonas (Vilnius : Contemporary Art Centre, 1999)
Antanavicius, Valentinas ; Cukermanas, Eugenijus Antanas ; Drazdauskaité, Laima ; Katiliuté, Ruta ; Katinas, Linas ; Kuras, Algimantas ; Pauksté, Vygantas ; Sauka, Sarunas ; Savickas, Augustinas ; Skackauskas, Algis ; Salkauskas, Mykolas ; Saltenis, Arvydas ; Vaitekunas, Povilas Ricardas ; Zimblyté, Kazimiera ; Serys, Vytautas ; Snipas, Mindaugas ; Jablonskis, Linas ; Puipa, Audrius ; Repsys, Petras ; Ars, Post ; Lankelis, Algis ; Urbonas, Gediminas ; Lapas, Zalias ; Lukenskas, Ceslovas ; Bubelyté, Violeta ; Balcytis, Vytautas ; Akstinas, Gediminas ; Jankauskas, Rimvidas ; Stanikas, Paulius ; Vaitkunas, Arunas ; Timakas, Gintautas ; Lukys, Alvydas ; Navakas, Mindaugas ; Umbrasas, Vytautas ; Kuizinas, Saulius ; Cerapas, Henrikas ; Gasiunas, Jonas ; Katinas, Dziugas ; Kempinas, Zilvinas ; Makarevicius, Gintaras ; Raila, Arturas ; Bastys, Darius ; Rakauskaité, Eglé ; Narkevicius, Deimantas ; Stanikas, Paulius ; Jankunas, Vytenis ; Jankauskas, Donatas ; Simelis, Ignas ; Barilaité, Jurga ; Rakauskaité, Eglé ; Urbonas, Gediminas ; Makarevicius, Gintaras ; Liskevicius, Dainius ; Narkevicius, Deimantas ; Novickas, Audrius ; Ziura, Darius ; Jurksaityté, Patricija ; Andrasiunas, Kestutis ; Simkus, Mindaugas ; Makarevicius, Gintaras ; Liskevicius, Dainius ; Beinaravicius, Augustinas ; Jansas, Evaldas ; Kempinas, Zilvinas ; Navakas, Mindaugas ; Tarasovas, Vladimiras ; Seputis, Gintaras ; Kumetaitis, Giedrius ; Jansas, Evaldas ; Simkus, Mindaugas ; Mazylis, Saulius ; Narkevicius, Deimantas ; Jansas, Evaldas ; Giroys, Darius ; Jankus, Karolis ; Raila, Arturas ; Liskevicius, Dainius ; Garbaciauskas, Algis ; Ceponyte, Aida ; Andrasiunas, Kestutis
biografie
Lithuanian Art 1989-1999 : The Ten Years, Contemporary Art Centre, Vilnius, September 10 - October 24, 1999
Engels & Litouws
kunstcatalogus
Keywords: Litouwen